Service provision patterns by main diagnoses and characteristics of patients - Brennan DS, Spencer AJ, Szuster FSP (Blackwell Synergy, 2000)
Service provision patterns may be influenced not only by clinical oral health status leading to a diagnosis and treatment plan, but also by other variables such as patient characteristics. The main aim of this study was to investigate whether associations between services provided and patient factors would persist after controlling for the main presenting diagnosis or condition. A random sample of dentists surveyed in 1993–94 provided a response rate of 74%. Private general practitioners recorded service provision data from logs of 1–2 typical days of practice.